The FCF (Functional Continued Fraction) #cosh_(cf) (x;a)=cosh (x+a/cosh(x+a/cosh(x+...)))#. How do you prove that this FCF is an even function with respect to both x and a, together?and #cosh_(cf) (x; a) and cosh_(cf) (-x;a)# are different?

1 Answer
Aug 17, 2016

#cosh_(cf)(x;a)=cosh_(cf)(-x;a) and cosh_(cf)(x;-a)=cosh_(cf)(-x;-a) #.


As cosh values are #>=1#, any y here #>=1#

Let us show that y = cosh(x+1/y) = cosh(-x+1/y)

Graphs are made assigning #a = +-1#. The corresponding two
structures of FCF are different.

Graph for y = cosh(x+1/y). Observe that a = 1, x >=-1


Graph for y = cosh(-x+1/y). Observe that a = 1, x <=1


Combined graph for y = cosh(x+1/y) and y = cosh(-x+1/y)


Likewise, it is shown that y = cosh(-x-1/y) = cosh(-x-1/y).

Graph for y = cosh(x-1/y). Observe that a = -1, x >=1


Graph for y = cosh(-x-1/y). Observe that a = -1, x <=-1


Combined graph for y = cosh(x-1/y) and y = cosh(-x-1/y)